THE PRIMARY STUDY ON FISH AND SHRIMP LARVA AT THE UROUNDING WATERS OF ISLANDS BELONGING TO TRUONG SA ARCHIPALAGO, VIET NAM - Thu, Nguyen Thi; Ha, Tran Manh (Vietnam Journal of Marine Science and Technology, 2012)
Belonging to the Indo - Pacific tropical marine biodiversity Central, marine living communities at the coastal waters of Islands of Truong Sa Archipelago plays the important roles in conservation and cover distribution the breeds of marine living resources (including larva forms of shrimp, fish anf others) not only in this areas but also in the neughbour waters. However, due to far from mainlands, the studies on them is limited to now. Samples was collected at the 3 - 7 transects with long 100m to 30 - 50m deepth, where is around some island such as Nam Yet, Da Nam, big Truong Sa, Song Tu Tay ... There are two stations was located on every transect for sampling the species composition and individual numbers of larva. Samples was catched by net with 200µ diameter in the vertical drawing following the water colum. This primary results that were identified including 46 taxons of fish, shrimp and others larva. Most of them are belonging to the coral fish anh shrimp and the widely distribution ecological groups having high econimic value such as: Labridae, Scaridae, Nemipteridae, Nephridae, Palinuridae ... The spatial taxon of larva diversity distribution is not very regular every island. The taxon diversity at the big Truong Sa, Nam Yet, Da Nam ones is higher than the others with 18 - 31 taxons/island. The others is have only about 10 taxons/islands. The medium individual number of larva is rather higher than that in the other sites which is in nearshore water with about 300 inds/100m3. The highest concentration of inds number of fish and shrimp larva is at the stations having good coral reefs.